Globalisation, Gender, and Equity – Effects of Foreign Direct Investment on Labour Markets in Rural Indonesia - Karin Astrid Siegmann (Intervention. Zeitschrift fuer Ökonomie / Journal of Economics, 2006)
This study assesses the impact of foreign direct investment (FDI) on gendered labour markets in rural Indonesia. It focuses on the gender composition of the workforce, female and male workers' employment conditions and gender wage inequality. The research strategy of "between-methods triangulation" is chosen, denoting the combination of quantitative and qualitative types of data generation and analysis. Two underlying mechanisms have been identified. A "cost effect" associated with transnational corporations' (TNCs') greater orientation towards the world market is the preferential recruitment of, on average, lower paid female workers. In light of global competitive cost considerations, this appears as a rational strategy for TNCs. Conversely, foreign firms' advanced technological endowments relative to domestic companies require a well-educated workforce with technical skills. In light of these perspectives, gender gaps in education and, on average, women's weaker labour market attachment disadvantage female workers' employment in TNCs. Both effects are mediated by a "reproductive constraint". This refers to the asymmetric distribution of reproductive obligations between female and male household members, whereby female input into the domestic economy is more demanding relative to that of males.
Keywords: J16; J31; J81; F02; F21; B41; 330